Role of the pedestal position on the pedestal performance in AUG, JET-ILW and TCV and implications for ITER. (12th June 2019) - Frassinetti, L.; Dunne, M.G.; Sheikh, U.; Saarelma, S.; Roach, C.M.; Stefanikova, E.; Maggi, C.; Horvath, L.; Pamela, S.; de la Luna, E.; Wolfrum, E.; Bernert, M.; et al.
Abstract: The role of the pedestal position on the pedestal performance has been investigated in AUG, JET-ILW and TCV. When the pedestal is peeling-ballooning (PB) limited, the three machines show a similar behaviour. The outward shift of the pedestal density relative to the pedestal temperature can lead to the outward shift of the pedestal pressure which, in turns, reduces the PB stability, degrades the pedestal confinement and reduces the pedestal width. Once the experimental density position is considered, the EPED model is able to correctly predict the pedestal height. An estimate of the impact of the density position on a ITER baseline scenario shows that the maximum reduction in the pedestal height is 10% while the reduction in the fusion power is between 10% and 40% depending on the assumptions for the core transport model used. In other plasmas, where the pedestal density is shifted even more outwards relative to the pedestal temperature, the pedestal does not seem PB limited and a different behaviour is observed. The outward shift of the density is still empirically correlated with the pedestal degradation but no change in the pressure position is observed and the PB model is not able to correctly predict the pedestal height. On the other hand, the outward shift of the density leads to a significant increase of η e and η i (where η e, i is the ratio of density to temperature scale lengths, ) which leads to the increase of the growth rate of microinstabilities (mainly ETG and ITG) by 50%. This suggests that, in these plasmas, the increase in the turbulent transport due to the outward shift of the density might play an important role in the decrease of the pedestal performance.